2009
DOI: 10.1556/ceugeol.52.2009.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Pleistocene climate and environment reconstruction by the paleomagnetic study of a loess-paleosol sequence (Cérna Valley, Vértesacsa, Hungary)

Abstract: Four paleosol layers indicating wet and moderate periods and five loess layers indicating dry and cold climate were separated by different methods. The following climate cycle model, based on the development of the sediment sequence created by the influence of climatic, geologic and geomorphologic phenomena, was established by detailed paleomagnetic studies (e.g. anisotropy of magnetic susceptibility (AMS), isothermal remanent magnetization (IRM), frequency dependence of magnetic susceptibility (κ FD ), etc.):… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Magnetic susceptibility borehole logs contributed to clarifying the climatic conditions of individual Quaternary layers Bradák et al 2009). The distal provenance of thin tuff horizons (Paks Tephra, Bag Tephra) was determined by means of their detailed petrographic evaluation (Gábris et al 1991;Sági et al 2008).…”
Section: History Of Quaternary Research In Hungarymentioning
confidence: 99%
“…Magnetic susceptibility borehole logs contributed to clarifying the climatic conditions of individual Quaternary layers Bradák et al 2009). The distal provenance of thin tuff horizons (Paks Tephra, Bag Tephra) was determined by means of their detailed petrographic evaluation (Gábris et al 1991;Sági et al 2008).…”
Section: History Of Quaternary Research In Hungarymentioning
confidence: 99%
“…Finally, the magnetic identification and the widespread occurrence of greigite in the sediments of Lake Pannon were discussed in the papers of Babinszki et al (2007), Babinszki and Márton E (2009), and the magnetic method was applied to climatic and environmental reconstructions during the Pleistocene by Bradák et al (2009Bradák et al ( , 2010. In an earlier paper (Illés-Almár and Almár 2006) it was demonstrated that there is a North-South asymmetry in the thermospheric density with higher densities over the Northern hemisphere in average.…”
Section: Environmental Magnetismmentioning
confidence: 99%